AESTHETICS OF AI-BASED MULTIMODAL LITERARY WORKS IN A MULTICULTURAL LITERARY PERSPECTIVE - Wawan Hermawan; Linda Eka Pradita (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
This study examines the aesthetics of AI-based multimodal literary works from a multicultural literary perspective. The rapid development of generative artificial intelligence has transformed literary production from monomodal forms into multimodal works integrating text, visuals, audio, and interactivity within a unified digital ecosystem. This transformation raises critical questions regarding the construction of aesthetic meaning, cultural representation, and the relationship between human creativity and machine-generated expression. The research employed a qualitative descriptive-interpretative approach combined with library research and digital text analysis. The study applied interdisciplinary perspectives, including literary aesthetics, multimodal discourse analysis, AI aesthetics, posthumanism, and multicultural literary theory. Data consisted of AI-generated multimodal literary texts, visual elements, and interactive features collected from digital platforms. The findings reveal that AI-based literary aesthetics are hybrid, multimodal, and interactive in nature. AI-generated works demonstrate coherent narrative structures, systematic figurative language, and strong multimodal integration that enrich aesthetic experiences through immersive and participatory engagement. However, the aesthetic expressions tend to be repetitive, generic, and limited in emotional depth because they are primarily constructed through algorithmic patterns rather than human existential experience. From a multicultural perspective, AI literary works are capable of representing local cultural identities within global contexts, yet they also exhibit tendencies toward cultural simplification, stereotyping, and homogenization due to biases embedded in training data. The study concludes that AI-based literary aesthetics represent a new posthuman aesthetic paradigm resulting from human–machine collaboration, while simultaneously requiring critical multicultural approaches to maintain cultural sensitivity and diversity in digital literary production. Keywords: AI aesthetics, multimodal literature, generative artificial intelligence, multicultural literature, posthumanism.